Development and Validation of an HPLC-DAD Method to Determine Alkylphenols in Milk - Serenella Seccia; Irene Dini (Beverages, 2025)
While providing considerable societal and economic benefits, plastic packaging leads to global pollution and poses health risks. Plastic additives like alkylphenols (APs) can interfere with endocrine functions even at low concentrations. Therefore, developing and validating analytical methods for their routine dosage in foods is paramount. The present work validated a chromatographic method to quantify alkylphenols (4-tert-octylphenol, 4-n-octylphenol mono-ethoxylate, 4-n-octylphenol, and 4-n-nonylphenol) in milk. The analytical method uses Chem Elut S a rapid supported liquid extraction (SLE) cartridges to eliminate the matrix effect, and reverse phase chromatography linked to a Diode Array Detector (DAD) to dosage the alkylphenols. The method was validated using the strategy of accuracy profiling, a decision-making instrument that calculates the method’s total error, encompassing bias and standard deviation. The reliability of the test was defined by the lack at the retention times of the APs of interfering peaks, the close linear relationship between the independent and the dependent variables in the regression model, the excellent precision at each concentration level for intra-day and inter-day measurements, and the errors of the procedure (systematic and random) estimated within the pre-established acceptability limits (±10%). The minimal environmental impact and ease of execution suggest its use in routine analyses.